2016
DOI: 10.1002/cncr.30325
|View full text |Cite
|
Sign up to set email alerts
|

Differences in treatment goals and perception of symptom burden between patients with myeloproliferative neoplasms (MPNs) and hematologists/oncologists in the United States: Findings from the MPN Landmark survey

Abstract: BACKGROUNDThis analysis of the myeloproliferative neoplasm (MPN) Landmark survey evaluated gaps between patient perceptions of their disease management and physician self‐reported practices.METHODSThe survey included 813 patient respondents who had MPNs (myelofibrosis [MF], polycythemia vera [PV], or essential thrombocythemia [ET]) and 457 hematologist/oncologist respondents who treated patients with these conditions.RESULTSGreater proportions of physician respondents reported using prognostic risk classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 21 publications
(43 reference statements)
0
40
0
1
Order By: Relevance
“…In these chronic conditions, the apparent and sometimes striking mismatch between physician perception of and the patient's stated priority for management demonstrated in the landmark study is a matter for reflection and review if proven in a wider study (Figure 1). 126 Another interesting disconnection in our therapeutic strategies for these illnesses is well demonstrated in MF, where prognostic data are used only in deciding whether to consider transplantation or not.…”
Section: Resultsmentioning
confidence: 99%
“…In these chronic conditions, the apparent and sometimes striking mismatch between physician perception of and the patient's stated priority for management demonstrated in the landmark study is a matter for reflection and review if proven in a wider study (Figure 1). 126 Another interesting disconnection in our therapeutic strategies for these illnesses is well demonstrated in MF, where prognostic data are used only in deciding whether to consider transplantation or not.…”
Section: Resultsmentioning
confidence: 99%
“…Clear communication between the patient and physician is therefore essential if symptoms are to be recognized and managed. However, the Landmark study revealed that, similar to other oncology settings [64,65], there is often a marked discord between physician and patient perceptions of MPN, its treatment and impact, and how well these issues are discussed and communicated [26]. Particularly striking differences were found in aspects such as management, treatment goals, and expectations, with marked discord between what patients and physicians reported having been discussed.…”
Section: Impact Of Mpns On Patient-reported Outcomes (Pros)mentioning
confidence: 97%
“…Although progression is a concern, vascular risk has a stronger influence on a physician's therapeutic decision-making. 15 There are multifactorial contributions toward MPN-associated thrombosis, including age and thrombosis history, sex, cardiovascular risk, mutation type and burden, inflammatory stress, and other contributors. 16 However, risk classification is still conventional and somewhat generic.…”
Section: Risk Assessmentmentioning
confidence: 99%